Simulation of Knee-Joint Angle Measurement for Accelerometer-Based Human Body Motion Monitoring System Using Quartus II - Tukiran, Zarina; Fen, Gan Shin; Ab. Rahman, Munirah; Ahmad, Afandi (Evolution in Electrical and Electronic Engineering, 2020)
Knee angle measurement is important for investigating complex gait disorder, monitoring the progress of rehabilitation and provide the range of motion (ROM) during flexion or extension. The research presents an implementation of knee angle measurement in simulation by using Quartus II software. Verilog HDL is used to develop the modules of the knee angle measurement. There are ten groups of value have been used in this study. The result of the simulation is verified through the EDA tool. The knee angle measurement is compared with the value calculated by calculator. In the finding, the knee joint angle measurement in simulation has a ±17° difference as compared to the value calculated by the calculator. Thus, there is some improvement is needed to make the algorithm well suit with the healthcare applications. The benefit of this project is it can help the physiotherapists to measure the range of motion during stance and swing for treatment to regain the full function of range of motion.